La aplicación de medidas socioeducativas, para la rehabilitaciòn del adolescente es insuficiente - Pacheco Cueva., Luis Alberto (2016)
This problem of juvenile delinquency expands and originates in all the social classes and strata, whether they are the rich people or poor people in the society, but without a doubt, I can say that the people who lack of economic resources are more prone to commit crimes falling in the phenomenon of crime; clarifying that there are also other factors that influence such as abuse, family disintegration, unemployment, underemployment, and a lack of access to an excellent education, among others. As we know, juvenile delinquency is a problematic that awake different reactions in the world of law and in society. The orders by the low age of criminal responsibility and harsher penalties for those young people are a constant in our days. In order to eradicate the social phenomenon of juvenile delinquency, which is presented as a problem in growth, we believe that it is necessary to raise a legal reform aimed at extending the time of punishment in the implementation of the measures socio-educative referred to in subparagraphs a), (b) and (c) of the Article.370 Clause 3 of the Code of Children and Adolescents, Ecuador, in order to provide sufficient time to allow the juvenile offender rehabilitation in the process of joining the 5 society especially in crimes, when by resolution establish the responsibility of a teenager by a fact punishable as a criminal offense, or in cases of offenses in ordinary criminal law are punishable by imprisonment as provided by law, such as: murder, manslaughter, rape, etc.. For these reasons we believe that youth crime to be a social phenomenon, is a complicated and complex problem to solve but not impossible, so it is an arduous task to eradicate and binding on all state authorities. In particular we can say that the current time applied Socio-Educational Measures for the case of offenses that are ordinary criminal law punishable by imprisonment as: probation up to 12 months, semi internment regime liberty for up to 24 months and institutional confinement for up to four years is not enough for the rehabilitation of juvenile offenders.